Lack of Correlation between the Kinase Activity of LRRK2 Harboring Kinase-Modifying Mutations and Its Phosphorylation at Ser910, 935, and Ser955 - Ito, Genta (Public Library of Science, 2014)
Leucine-rich repeat kinase 2 (LRRK2) is extensively phosphorylated in cells within a region amino-terminal to the leucine-rich repeat domain. Since phosphorylation in this region of LRRK2, including Ser910, Ser935, Ser955, and Ser973, is significantly downregulated upon treatment with inhibitors of LRRK2, it has been hypothesized that signaling pathways downstream of the kinase activity of LRRK2 are involved in regulating the phosphorylation of LRRK2, although the precise mechanism has remained unknown. Here we examined the effects of LRRK2 inhibitors on the phosphorylation state at Ser910, Ser935, and Ser955 in a series of kinase-inactive mutants of LRRK2. We found that the responses of LRRK2 to the inhibitors varied among mutants, in a manner not consistent with the above-mentioned hypothesis. Notably, one of the kinase-inactive mutants, T2035A LRRK2, underwent phosphorylation, as well as the inhibitor-induced dephosphorylation, at Ser910, Ser935, and Ser955, to a similar extent to those observed with wild-type LRRK2. These results suggest that the kinase activity of LRRK2 is not involved in the common mechanism of inhibitor-induced dephosphorylation of LRRK2.